Developing Preventive, Curative and Recovery (PCR) Strategy for Managing COVID-19 - Aprajita Kumari; Vikash Kumar (Issues and Development in Health Research Vol. 2, 2021)
The re-occurring waves of COVID-19 pandemic has taken so many lives all over the world. Some country has managed it very well whereas some is still struggling to manage it. Along with medications, modification in lifestyle and proper diet may be the two powerful weapons to fight COVID-19 infection. Present paper highlights the management strategy to deal with the COVID-19 pandemic. This strategy is named as Preventive, Curative and Recovery (PCR) strategy which any individual can apply personally to stay safe during such a harsh situation. Preventive strategy includes the actions to be taken to keep the virus away from the internal environment of the body. Curative action begins when the body encounters infection. Recovery is the process of gaining the lost strength by the body. The paper attempts to develop a model for all the three together to be named as PCR Model.